Gambaran Penolong Persalinan, Logistik Vaksin Dan Dukungan Keluarga Pada Cakupan Imunisasi Hepatitis B 0 -7 Hari Puskesmas Sangkub Kabupaten Bolaang Mongondow Utara Tahun 2006- 2008 - Inaku, Hartati (Jurnal Pelangi Ilmu, 2009)
Hepatitis Disease is contagion which caused by this Hepatitis B Penyakit virus still be one health problems in Indonesia because the prevalence enough heights. Preventive priority to this disease that is through giving of immunization Hepatitis at baby and children. This thing is meant that they are protected against infection .of Hepatitis B early possible in life.